Hearing and ear status of Pacific children aged 11 years living in New Zealand: the Pacific Islands families hearing study. (1st February 2019) - Purdy, Suzanne C.; Taylor, Steve; Schluter, Philip J.; Tautolo, el-Shadan; Iusitini, Leon; Ahmad, Zahoor; Sundborn, Gerhard; Paterson, Janis
Abstract: Objective: This study aimed to determine the prevalence of hearing loss and ear problems in Pacific children, and investigate current and past demographic, health and social factors potentially associated with hearing and ear problems. Design: A cross-sectional observational study design nested within a birth cohort was employed. Study sample: Nine-hundred-twenty Pacific children aged 11 years were audiologically assessed. Using average hearing thresholds at 500, 1k and 2k Hz, 162 (18%) right and 197 (21%) left ears had ≥20 dB hearing loss. Hearing loss was mild (20–39 dB) in most cases; 2% of ears had moderate to moderate-severe (40–69 dB) hearing loss. However, only 101 (11%) children had normal peripheral hearing defined by passing hearing threshold, tympanogram and distortion product otoacoustic emission assessments. Those with confirmed middle ear disease at age 2 years had significantly increased odds of a non-Type A tympanogram (adjusted odds ratio: 2.00; 95% confidence interval: 1.56, 2.50) when re-assessed at age 11 years. Conclusions: Hearing loss, abnormal tympanograms, and auditory processing difficulties were present in many Pacific children. Interventions are also urgently needed to mitigate the effect of the longstanding ear disease likely to be present for many Pacific children.